Thickness-Dependent Photocatalysis of Ultra-Thin MoS2 Film for Visible-Light-Driven CO2 Reduction - Yi-Fan Huang (MDPI AG, 2021)
The thickness of transition metal dichalcogenides (TMDs) plays a key role in enhancing their photocatalytic CO2 reduction activity. However, the optimum thickness of the layered TMDs that is required to achieve sufficient light absorption and excellent crystallinity has still not been definitively determined. In this work, ultra-thin molybdenum disulfide films (MoS2TF) with 25 nm thickness presented remarkable photocatalytic activity, and the product yield increased by about 2.3 times. The photocatalytic mechanism corresponding to the TMDs’ thickness was also proposed. This work demonstrates that the thickness optimization of TMDs provides a cogent direction for the design of high-performance photocatalysts.